User Satisfaction on Graduate Competence: Insight form Islamic Banking Alumni, 2019-2024 - Fitri, Cut Elda Ram; Hasnita, Nevi; Fitria, Ana (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
This study aims to analyze user satisfaction and graduate performance of the Islamic Banking Department of Universitas Islam Negeri Ar-Raniry Banda Aceh in the 2019–2024 period as an effort to improve graduate quality and department accreditation. The issues raised include the suitability of graduate competencies to the world of work, waiting time to get a job, and the scope of work areas. The method used is a combination of a descriptive quantitative approach through the distribution of questionnaires to 100 alumni and 50 graduate users, and a qualitative approach through in-depth interviews with users from the Islamic finance sector, government institutions, and multi-finance. The results show that the majority of graduates are absorbed into the world of work in less than six months, with internship experience being a significant factor in accelerating this process. The majority of alumni work at the national and local levels, while a small number have penetrated the national job market. Graduate users assess that alumni have a good work ethic, adequate mastery of technology, and appropriate technical skills, but still need improvement in public communication and foreign language proficiency. The conclusion of this study indicates that graduates of the Islamic Banking department are well-prepared for work, and that practice-based learning, such as internships, and an efficient study period are key to improving graduate quality. These results provide a strategic foundation for curriculum development and improving the department's accreditation toward excellence.